Memory, Music and Religion: Morocco's Mystical Chanters. Earl H. Waugh. 2005. Columbia, SC: University of South Carolina Press:. xix, 260 pp. illustrations, musical examples, glossary, index. ISBN-10 1570035679. ISBN-13 9781570035678. - Watkins, Lee (International Library of African Music, 2010)
pages: 125-130
Keywords: African Music